Self Assessment of The Risk of Covid-19 Transmission using The Inarisk Personal Application - Sutriningsih, Ani; Ardiyani, Vita Maryah; Andinawati, Mia (Journal of Community Service for Health, 2022)
One way to break the chain of spread of Covid-19 is through the InaRISK application. Knowledge of nursing students about this application is still low. BNPB entered Covid-19 into the InaRISK application at April 2020. Its function is to find out how the state of the area around us, whether it is included in the yellow, red or green zone. In addition, the community can conduct an independent assessment regarding the need or not to conduct a rapid test through the InaRISK application. The purpose of this activity was to provide counseling about InaRISK Personal application and measure the risk of Covid-19 of students. The method used by giving counselling about InaRISK Personal application through lectures to 36 students at Faculty of Health Sciences. The results of the self-assessment showed based on the statement of potential for infection outside the home, most participants (88.9%) touched objects/money that were also touched by other people. Based on the statement of potential for infection in the house, most participants (86.1%) did not install hand sanitizer in front of the entrance, to clean their hands before holding the handle (handle at the house entrance). Based on the statement of endurance (immunity) all participants (100%) were under 60 years old and almost all participants (94.4%) did not have diseases: heart/diabetes/chronic respiratory disorders. The risk of participants being exposed to Covid-19 were based on the InaRISK Personal application, almost half of participants (44.4%) were in the low-risk category. Based on the measurement results, it could be concluded that the potential risk of Covid-19 transmission using the InaRISK Personal self-assessment on students had a low risk of 44.4%. The campus is expected to hold counseling programs or health promotions on a regular basis to provide information so that it can increase student knowledge.